Effect of Zinc and DHA on Expression Levels and Post-Translational Modifications of Histones H3 and H4 in Human Neuronal Cells - Sadli, Nadia; Ahmed, Nayyar; Ackland, M. Leigh; Sinclair, Andrew; Barrow, Colin J.; Suphioglu, Cenk (IntechOpen, 2011)
None